2019
DOI: 10.1111/jth.14426
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phosphorylation of von Willebrand factor by FAM20c enhances its ability to support platelet adhesion

Abstract: comes indicate that VWF can be phosphorylated by FAM20c in vitro, and this novel post-translational modification enhances the adhesiveness of VWF to platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Fam20C has been found to directly phosphorylate fibrinogen alpha and gamma chains in vitro ( 56 ), and further work is needed to define the physiological roles of the phosphorylation events. On a similar note, Fam20C phosphorylates the A2 domain of von Willebrand factor (vWF) on two SxE sites, pSer1517 and pSer1613 ( 90 ). The modifications promote platelet adhesion to sites of vascular injury and helps in coagulation ( 90 ).…”
Section: Fam20c the Secreted Golgi Casein Kinasementioning
confidence: 96%
“…Fam20C has been found to directly phosphorylate fibrinogen alpha and gamma chains in vitro ( 56 ), and further work is needed to define the physiological roles of the phosphorylation events. On a similar note, Fam20C phosphorylates the A2 domain of von Willebrand factor (vWF) on two SxE sites, pSer1517 and pSer1613 ( 90 ). The modifications promote platelet adhesion to sites of vascular injury and helps in coagulation ( 90 ).…”
Section: Fam20c the Secreted Golgi Casein Kinasementioning
confidence: 96%
“…Furthermore, FAM20C-mediated phosphorylation of oocyte secreted bone morphogenetic protein 15 and growth differentiation factor 9 is essential for regulation of their activity in folliculogenesis and ovulation [ 6 ]. Likewise, FAM20C-mediated phosphorylation of von Willebrand factor increased platelet adhesion [ 7 ], and lack of FAM20C phosphorylation of histidine-rich calcium binding protein causes ventricular arrhythmia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The A domains have three S‐x‐E sites that were surveyed in the study. They found that both S1517 and S1613 in the A2 domain were phosphorylated by active FAM20c in vitro . When assessing the phosphorylation state of VWF purified from healthy donor plasma, they validated that S1613 could be phosphorylated in vivo, though the relative abundance compared to that of nonphosphorylated S1613 is not clear.…”
mentioning
confidence: 99%
“…A recent investigation performed by Da et al provides evidence that von Willebrand factor (VWF) can be phosphorylated in the A2 domain, a modification that has never before been observed . VWF is a multimeric glycoprotein that mediates platelet adhesion to the endothelium upon vascular injury, a process critical for hemostasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation